Effect of Plastic Mulch and Pesticide Application on Chemical Properties of Andisol - Maulana Insanul Kamil; Dina Oktaviani; Annisa Rachim; Khairun Nisa Kamarudin; Irwin Mirza Umami; Eti Farda Husin; Hermansah Hermansah (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2020)
The application of plastic mulch and pesticides is common practice in intensive agriculture in Indonesia. However, their effects on soil fertility are still uncertain. Therefore, this study was aimed to determine the effect of plastic mulch and pesticide application on the soil fertility of Andisol. The experiment was conducted in an intensive agriculture field in West Sumatra and the treatments included were: plastic mulch and pesticide application with two levels of each. Treatments were arranged in a completely randomized design with three replications. The result shows that there were significantly high in pH, total N and exchangeable Mg when using plastic mulch while organic C was found to be low in a plot with the application of pesticide. Meanwhile, the interaction between plastic mulch without pesticide showed a significantly higher in exchangeable Mg. The result suggested that the plastic mulch practice can sustain the availability of nutrients in the soil while the usage of pesticides can reduce the organic C in the soil besides its main function to protect the crops.